Performance and mineral requirements of indigenous Caninde goats - Ribeiro, L. P. S. (2018)
Thirty-three castrated male Caninde goat kids (15.7 +/- 0.41 kg) that were approximately 5 months old were used to estimate the body composition and dietary requirements of macrominerals (Ca, P, Mg, Na and K) and microminerals (Cu, Mn, Fe and Zn). Goat kids were distributed in a complete randomized design with four levels of feeding (0, 20, 40 and 60% feed restriction). Five animals were slaughtered at the start of the trial to serve as a baseline group and were used to estimate the initial body composition as well as to calculate mineral retention. Body composition was fit using a logarithmic equation in the form of a nonlinear model. Feed restriction reduced mineral intake and empty body weight gain in animals. The mineral composition of the bodies of Caninde goats weighing 15 to 25 kg ranged from 14.6 to 17.6 Ca, 6.15 to 4.97 P, 0.34 to 0.36 Mg, 1.62 to 1.54 K, 3.69 to 3.15 Na (g/kg EBW), 3.71 to 7.57 Cu, 3.02 to 8.44 Mn, 38.0 to 32.2 Fe, and 10.5 to 14.2 Zn (mg/kg EBW). Performance growth was reduced by feed restriction. The net mineral requirements of Caninde goat kids increased with body weight and it seems to be overestimated when is comparing from those recommended by international feed systems, which can be due the data base (e.g. animal species) used to create the systems; thus, the nutritional requirements of minerals presented in this research may contribute to mineral supplementation in growing goats.